Analysis of Aceh's Economic Recovery After the Tsunami Disaster and Prolonged Conflict Year, 2005 - Abdul Azis*; Nurasiah Nurasiah; Zulfan Zulfan; Teuku Kusnafizal; Rizal Fahmi; Yusrijal Abdar (Riwayat: Educational Journal of History and Humanities, 2023)
The article entitled Analysis of Aceh's Economic Recovery Post-Tsunami and Prolonged Conflict in 2005-2013, aims to analyze changes and developments in the Acehnese economy after experiencing natural disasters in the form of the tsunami and the prolonged conflict that occurred before the tsunami. This article uses a qualitative approach and is assisted by historical methods. The technique used in this article is a literature study technique. The results obtained in this study are the changes and economic developments of the Aceh province with the data that has been obtained in the literature study conducted. The economy in the first year after the tsunami can be seen that the Acehnese economy is in a very chaotic condition, even reaching minus in 2005 and becoming the region with the lowest economy in all of Indonesia. However, gradually Aceh began to rise from various sectors, be it economy, education, infrastructure, began to be built and progressed after the natural disaster and prolonged conflict.